Improving Invoice Management: A Web-based Application for the Hospitality IT Vendor Industry using Prototyping Model - Jansen Wiratama; Santo Fernandi Wijaya; Hari Santoso; Jonathan (Jurnal Informatika Ekonomi Bisnis, 2023)
This research delves into the challenges faced by a hospitality IT vendor providing services to a diverse clientele in Indonesia. The vendor, relying on profits from clients for operational and developmental activities, needs help with the billing process. The complexities arise from various payment schemes, including full payments and installments, coupled with the annual requirement for clients to purchase a maintenance key for continued system access. The existing transaction process experiences delays due to difficulties searching for invoice data among numerous clients with varying payment times. These delays hinder the timely collection of subsequent payments, resulting in receivables and potential disruptions to the vendor's cash flow for operational and developmental costs. Traditional bill recording methods compound the problem with inaccuracies and data retrieval challenges The findings of this research is a web-based application developed through the SDLC prototyping model to address these issues. The application, evaluated through User Acceptance Testing (UAT), successfully overcame the challenges. The results indicate that the application efficiently manages invoice data, facilitates timely payments, and enhances overall accuracy in data processing. In conclusion, the web-based application is an optimal solution, resolving invoice management issues and streamlining processes for the hospitality IT vendor.